Experimental investigation on ultrasonic vibration-assisted manufacturing of fiber-reinforced thermoplastics. Issue 7 (19th May 2022) - Kalyan Kumar, R.; Omkumar, M.
ABSTRACT: The ultrasonic energy-assisted manufacturing of fiber-reinforced thermoplastics is gaining importance in recent years because of its quicker heat generation with less energy requirement than other heating methods. However, a semi-finished raw material such as prepreg or preform with prior processing method is predominantly used. This study investigates the manufacturing of fiber-reinforced thermoplastics from dry and solid raw materials using the ultrasonic plastic welding process. Layers of dry thermoplastics and woven roving synthetic fibers are stacked successively and consolidated with high-frequency ultrasonic vibrations. Influential process settings were experimentally realized for different material stacking sequences to obtain a uniform fusion bonding in thermoplastics. The cross-sectional morphology reveals a strong interfacial attraction between fibers and matrix for the higher contact pressure of the ultrasonic horn along with a longer hold duration that promoted an effective resin impregnation through wetting and intermolecular diffusion in thermoplastics, thereby reducing the void contents and increasing the fiber volume in composites. Furthermore, the tensile, flexural, and interlaminar strength of composites are determined and compared with those obtained using the compression molding process. The thermogravimetric and differential scanning calorimetry data provided thermally stable composites. An efficacious composite with substantial properties was manufactured in a cycle time of 10 s.